Challenges Facing the Teaching and Learning of Macramé Household Crafts in Tertiary Institutions in Abia State, Nigeria - Ogonna Egbuchulam; Priscilla Ezema (International Journal of Home Economics, Hospitality and Allied Research)
The purpose of this study was to identify the challenges in teaching and learning of Macramé household crafts and develop a suitable instructional manual for teaching macramé household crafts in tertiary institutions in Abia State, Nigeria. The study adopted Research and development (R and D) method. The study area was tertiary institutions in Abia State. Eighteen lecturers and forty-one students formed the population for the study making a total of fifty-nine subjects. Data obtained from the study through a well-structured questionnaire were analysed using mean and standard deviation while the hypotheses were tested using Mann-Whitney-Wilcoxon Test. The result revealed seven challenges being encountered in teaching crafts in the institutions. The study also showed that out of the fourteen challenges identified, thirteen challenges were encountered by students in the institutions while learning macramé household crafts. Overall, the study shows that no statistically significant difference exists between the challenges encountered in teaching and learning of macramé household crafts in tertiary institutions in Abia State, hence the need for an improvement. The study further developed and examined an instructional manual for teaching macramé household crafts which the lecturers confirmed will help in improving the teaching and learning of macramé crafts. All the null hypotheses were accepted, meaning that there is no statistically significant difference between the mean responses of Home Economics lecturers in both the Universities and those in the College of Education.